Practical Guidelines for Collection, Manipulation and Inactivation of SARS‐CoV‐2 and COVID‐19 Clinical Specimens. Issue 1 (5th June 2020) - Bain, William; Lee, Janet S.; Watson, Alan M.; Stitt‐Fischer, Molly S.
Abstract: SARS‐CoV‐2 is a novel coronavirus that causes the acute respiratory disease—Coronavirus disease 2019 (COVID‐19)—which has led to a global health crisis. Currently, no prophylactics or therapies exist to control virus spread or mitigate the disease. Thus, the risk of infection for physicians and scientists is high, requiring work to be conducted in Biosafety Level‐3 (BSL‐3) facilities if virus will be isolated or propagated. However, inactivation of the virus can enable safe handling at a reduced biosafety level, making samples accessible to a diverse array of institutions and investigators. Institutions of all types have an immediate need for guidelines that outline safe collection, handling, and inactivation of samples suspected to contain active virus. Here we provide a practical guide for physicians and researchers wishing to work with materials from patients who are COVID‐19 positive or suspected positive. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Practical guidelines for the safe collection and handling of specimens collected from COVID‐19 and suspected COVID‐19 patients Basic Protocol 2 : Inactivating SARS‐CoV‐2